Preclinical pharmacokinetic characterization of amdizalisib, a novel PI3Kδ inhibitor for the treatment of hematological malignancies - Jiang, Shuwen; Li, Xiangkun; Xue, Weifang; Xia, Sumei; Wang, Jian; Sai, Yang; Dai, Guangxiu; Su, Weiguo (Frontiers in Pharmacology, 2024)
Amdizalisib, also named as HMPL-689, a novel selective and potent PI3Kδ inhibitor, is currently under Phase II clinical development in China for treating hematological malignancies. The preclinical pharmacokinetics (PK) of amdizalisib were extensively characterized in vitro and in vivo to support the further development of amdizalisib. We characterized the plasma protein binding, blood to plasma partition ratio, cell permeability, hepatic microsomal metabolic stability, and drug-drug interaction potential of amdizalisib using in vitro experiments. In vivo PK assessment was undertaken in mice, rats, dogs, and monkeys following single intravenous or oral administration of amdizalisib. The tissue distribution and excretion of amdizalisib were evaluated in rats. The PK parameters (CL and Vss) of amdizalisib in preclinical species (mouse, rat, dog and monkey) were utilized for the human PK projection using allometric scaling approach. Amdizalisib was well absorbed and showed low to moderate clearance in mice, rats, dogs, and monkeys. It had high cell permeability without P-glycoprotein (P-gp) or breast cancer resistance protein (BCRP) substrate liability. Plasma protein binding of amdizalisib was high (around 90%). It was extensively distributed but with low brain to plasma exposure ratio in rats. Amdizalisib was extensively metabolized in vivo and the recovery of the prototype drug was low in the excreta. Amdizalisib and/or its metabolites were primarily excreted via the bile and urine in rats. Amdizalisib showed inhibition potential on P-gp, but not on BCRP, and was observed to inhibit CYP2C8 and CYP2C9 with IC50 values of 30.4 and 10.7 μM, respectively. It exhibited the induction potential on CYP1A2, CYP2B6, CYP3A4 and CYP2C9. The pre-clinical data from these ADME studies demonstrate a favorable pharmacokinetic profile for amdizalisib, which are expected to support the future clinical development of amdizalisib as a promising anti-cancer agent.